[tex]\\ \bull\longmapsto 4x-1=3y+5[/tex]
[tex]\\ \bull\longmapsto 4x-3y=6[/tex]
X. intercept
[tex]\\ \bull\longmapsto 4x=6+3y\implies x=\dfrac{3y+6}{4}[/tex]
Now
[tex]\\ \bull\longmapsto x=\dfrac{3(0)+6}{4}=\dfrac{6}{4}=\dfrac{3}{2}[/tex]
Hence
[tex]\\ \bull\longmapsto x-intercept=\left(\dfrac{3}{2},0\right)[/tex]
Y intercept:-
[tex]\\ \bull\longmapsto 3y=4x-6\implies y=\dfrac{4x-6}{3}[/tex]
Put 0 on x
[tex]\\ \bull\longmapsto y=\dfrac{4(0)-6}{3}=\dfrac{-6}{3}=-2[/tex]
Hence.
[tex]\\ \bull\longmapsto y-intercept=(0,-2)[/tex]